Hydroxypropylmethylcellulose at the oil-water interface. Part II. Submicron-emulsions as affected by pH - Camino, Nerina Andrea (2011)
The emulsifying behavior of four different commercial types of hydroxypropylmethylcellulose (HPMC) was studied and correlated with the properties of the interfacial films. Emulsions resulted multimodal when made by a high speed blender (Ultraturrax, UT), with droplets higher than 10 μm. The average diameters D32 resulted higher for UT emulsions stabilized by the higher molecular weight HPMC (E4M and E50LV). However, E4M emulsions presented the highest variation in D32 with pH. Emulsions made by high intensity ultrasound, presented a monomodal population with the majority of the droplets around 0.3 μm. In all cases, the droplets sizes were smaller than 0.5 μm. As for UT emulsions, higher average diameters (D32 and D43) were obtained for all HPMCs at pH3.Emulsions at pH3 destabilized quicker than emulsions at pH6, mainly when made by Ultraturrax. At pH3 hydrophobic interactions are impeded thus elastic films are not formed upon emulsification, resulting in droplets with higher initial diameters than at pH6.